Creative Testimony and Post-War Dissociation: Witnessing the Shifting Body of Trauma in Gertrude Stein's The Autobiography of Alice B Toklas and the Writings of Kay Sage - Callaghan, Echo (Trinity College (Dublin, Ireland). School of Languages, Literature and Cultural Studies, 2021)
Creative Testimony and Post-War Dissociation: Witnessing the Shifting Body of Trauma in Gertrude Stein's The Autobiography of Alice B Toklas and the Writings of Kay Sage – Echo Meredith Callaghan The impact of the trauma inflicted upon male soldiers during the First and Second World Wars on the writing of male members of the Surrealist movement has been well documented by literary theorists. In contrast, the impact of the trauma of the two World Wars upon the writing of female Surrealists has not received the same level of scrutiny. This dissertation utilises contemporary ideas in the fields of psychology and neuroscience, alongside research into the genres of autobiography and testimony, in order to analyse the ways in which two female Surrealist writers, Gertrude Stein and Kay Sage, responded to the trauma they witnessed in their respective post-war societies. Van Der Kolk describes the feeling of dissociation as 'the essence of trauma' (2014: 66) and an attempt to express the traumatic phenomenon of dissociation can be identified in the autobiographical writing of Stein and Sage. Their works testify to large-scale changes in the ways that society was conceptualising and experiencing the body as a result of the trauma of war. Society at this time lacked the understanding and medical terminology to express and explain the effects of trauma and, as a consequence, both women resort to using elements of fiction in their work to facilitate their discussions. They employ fiction to investigate and verbalise the consequences of trauma, analyse the inherent instability of memories affected by trauma, imagine literary witnesses for themselves and to therapeutically reconstruct their past. As a result, this dissertation will argue that their writing amounts to a form of creative testimony, which blurs the boundaries between fictional and testimonial writing and asks fundamental questions about the nature of fiction and its position as a therapeutic tool.
Keywords: Identities and Cultures of Europe